Rodzicielstwo adolescentów z zaburzeniami – nowa ścieżka życia - Bublil , Granit (Studia Edukacyjne, 2019)
The objective of the article is to present a group intervention program in the narrative approach with parents of adolescents who suffer from attention deficit hyperactivity disorder (ADHD). For this purpose, the article will review the characteristic difficulties of parents of adolescents who have ADHD, the principles of the narrative approach, and the contribution of the group in work in this approach. On this basis, the initial intervention program, which addresses unique components intended to answer the difficulties and content worlds of this population of parents, will be presented. This article will express the parents’ strengths and the difficulties that they face and the group processes that influenced the change in the perceptions and behaviors of parents of adolescents with ADHD. These contents were learned from the pilot group of the research study. Five parents, primarily mothers, of children aged twelve to fourteen who suffer from ADHD participated in the group. The article will address one of the significant difficulties that arose in the encounters with the parents, the behavior of the adolescent who has ADHD regarding the religious identity and behavior appropriate for the values upon which he was educated. The contribution of the research study lies in that it offers parents support and ways of coping with the stress and emotional load that accompanies their coping with the adolescent who has ADHD.